Pancasila di Atas Piring: Merefleksikan Nilai-Nilai Kebangsaan dalam Kuliner Nusantara - Haifa Khansa Khaisya; Ratna Fitria; Ratri Assyifa Putri; Railivan Lintang Diaz Yudistiagis; Widya Nurin Syarafina (Jurnal Pendidikan Non formal, 2025)
Pancasila as the basis of Indonesia has been rooted in the traditions of the archipelago and has been reflected in daily life for a long time, including traditional cuisines. This quantitative research analyzed the role of Indonesian food as a representation of cultural identity amid the challenges of globalization that eroded national identity, especially in the younger generation due to westernization and individualism. The results showed that Indonesian food had a significant impact as an element of national identity. It has a position that is as important as the various types of cultural instruments in Indonesia. The preservation of Indonesian cuisine is a collective responsibility that must be supported through education, community involvement, and the contribution of the younger generation, so that the cultural value, unity, and identity of the nation remain in the midst of a wave of globalization.